Proses Pembuatan Tepung Jamur Tiram Putih (Pleurotus ostreatus) Dengan Pengaruh Lama Waktu Perendaman dan Konsentrasi CaCO3 - Widodo, Agus Slamet, Dr. Siti Chalimah, M.Pd (2015)
White oyster mushrooms (Pleurotus ostreatus) is one of the current consumption of mushrooms that quite popular and it's preffered for almost people, because it tastes delicious and also full of nutrients, high protein, and low fat. Oyster mushrooms has low storability after harvested. This is due cause the white oyster mushroom has a high water content, it is necessary to do an effort to extend the shelf life of white oyster mushroom. Molecules of CaCO3 will soon bind water molecules contained in the plant tissue and will form calcium hydroxide, strengthen plant tissue. The purpose of research, 1) Knowing the effect of lenggth soaking time and concentration different CaCO3 to the quality of JTP flour. 2) Knowing the best treatment among the length soaking time and the concentration of CaCO3 differently to manufacture JTP flour. The method used in this study is a research method experiment with completely randomized design (CRD) using two factors. The first factor is the length soaking time 5, 10 and 15 minutes. The second factor is the concentration of CaCO3 as much as 3%, 5% and 7%. Data analysis using ANOVA with two lanes. Results of data analysis obtained the best treatment at a concentration of CaCO3 as much as 3% with length soaking time 10 minutes, carbohydrate levels as much as 34.26%. Best water content results in soaking 15 minutes with a concentration of CaCO3 as much as 7%, amounting to 50.2%.